Non-Invasive Hormonal Monitoring in Wildlife (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2024)
Non-invasive hormonal monitoring has emerged as a cornerstone methodology in wildlife biology and conservation science, enabling researchers to quantify physiological stress, reproductive status, and metabolic function across diverse taxa without the confounds introduced by capture-related distress. This study systematically evaluated the analytical reliability, cross-species applicability, and conservation utility of four principal non-invasive matrices - fecal glucocorticoid metabolites (FGM), urinary immunoreactive cortisol, saliva-derived testosterone, and hair cortisol concentrations - across twelve mammalian species occupying protected and human-modified landscapes in Central Europe and East Africa. Enzyme immunoassay (EIA) and radioimmunoassay (RIA) procedures were validated for each matrix-species combination using adrenocorticotropic hormone (ACTH) challenge tests and parallelism assays. FGM concentrations differed significantly between protected-area and fragmented-habitat populations (F = 18.74, p < 0.001), with species inhabiting anthropogenically disturbed zones exhibiting mean glucocorticoid output 43.6% above baseline values recorded in undisturbed reserves. Hair cortisol provided the most temporally integrated stress signal (r = 0.81, p < 0.001), while urinary cortisol reflected acute perturbations with a lag of 4-6 hours. Reproductive hormones quantified from fecal samples successfully delineated oestrous cycle phases in five ungulate species with 88.4% concordance against reference blood serum data. These findings validate a multi-matrix non-invasive endocrinology framework capable of supporting population-level health surveillance, captive breeding optimisation, and landscape-scale conservation planning without requiring physical animal contact.